Rez ball - Graves, Byron (2023)
"These days, Tre Brun is happiest when he is playing basketball on the Red Lake Reservation high school team--even though he can't help but be constantly gut-punched with memories of his big brother, Jaxon, who died in an accident. When Jaxon's former teammates on the varsity team offer to take Tre under their wing, he sees this as his shot to represent his Ojibwe rez all the way to their first state championship. This is the first step toward his dream of playing in the NBA, no matter how much the odds are stacked against him. But stepping into his brother's shoes as a star player means that Tre can't mess up. Not on the court, not at school, and not with his new friend, gamer Khiana, who he is definitely not falling in love with. After decades of rez teams almost making it, Tre needs to take his team to state. Because if he can live up to Jaxon's dreams, their story isn't over yet" --
Keywords: Ojibwa Indians -- Juvenile fiction; Teenage boys -- Juvenile fiction; Basketball stories; Young adult fiction; Fiction; Juvenile works; Novels; Sports fiction; Young adult fiction; Sports fiction; Novels; Romans